An efficient synthesis of multisubstituted 4-nitrobuta-1, 3-dien-1-amines and application in cyclisation reactions. Issue 21 (24th May 2018) - Vigante, Brigita; Plotniece, Aiva; Rucins, Martins; Petrova, Marina; Muhamadejev, Ruslan; Pajuste, Karlis; Belyakov, Sergey; Shermolovich, Yuriy G.; Sobolev, Arkadij
Abstract: The synthesis of multisubstituted 4-nitrobuta-1, 3-dien-1-amines (nitrodienamines) from 3-aminocrotonates and nitroacetaldehyde potassium salt, has been performed in 45–89% yields. This one-step protocol works efficiently with a broad range of N-H and N-substituted 3-aminocrotonates and delivers both primary and secondary nitrodienamines. In addition, the possible variations of the substituents at the positions 2 and 3 of 4-nitrobuta-1, 3-dien-1-amine have been shown. Generally, the yields of secondary 4-nitrobuta-1, 3-dien-1-amines were lower than those of primary ones. The synthetic usefulness of obtained 4-nitrobuta-1, 3-dien-1-amines has also been demonstrated by achieving the synthesis of multisubstituted 5-nitro-1, 6-dihydropyridines in two-component cyclocondensation reactions of 4-nitrobuta-1, 3-dien-1-amines with aromatic or aliphatic aldehydes. Lastly, diverse N-H and N-substituted 5-nitro-1, 6-dihydropyridines have been obtained in 35–87% yields. Graphical abstract: